Kallanai And the Evolution of Irrigation In Tamil Nadu - Subha, R.; Reena, K (Journal of Neonatal Surgery, 2025)
This research investigates the historical relevance and modern relevance of the Kallanai Dam, a necessary irrigation system in Tamil Nadu, and its history. The research aimed to uncover the process of how the knowledge and use of the irrigation procedure of the dam has developed in hindsight from the past to the current and the role these changes have had on the livelihoods and economies of the region. Data collection was done through a quantitative survey as a means of determining the information needed; the use of a questionnaire administered to 67 respondents. In order for there to be diverse representation, Stratified random sampling was employed, by considering the number of years a respondent had been associated with irrigation systems. Through the use of SPSS, the study performed a statistical analysis by use of One-Way ANOVA, One-Sample t-Test and the Friedman Test to explore significant differences regarding people’s perceptions in various groups. It was found that there were significant differences in perceptions on Kallanai’s engineering, agricultural benefits, and historical merit mainly, based on the respondent sessions of experience (Rathika, 2016). Experience of more than 16 years was accompanied by an elevated understanding of the continued importance of the dam and the importance of its preservation. The findings confirm the concept that education of the people on ancient irrigation methods can be the way out of the gap between generations. The study suggests that an integration of traditional methods into present water governance strategies could be used to solve contemporary problems without sacrificing Tamil Nadu’s future development.